Error analysis of case formation in sinhala spoken by tamils - applied linguistics approach - Shiromi, M. (University of Jaffna, 2016)
This study aims to identify the types of morphological errors in case formation in Sinhala spoken by Tamils. Generally, many scholars have done contrastive studies of Tamil and Sinhala in Sri Lanka but an error analysis of Sinhala spoken by Tamils has not been done yet. Error analysis is crucial for evaluating language application. In this way, the data for this study was collected from specific speaking activities done by randomly samples of 50 students who are learning Sinhala and direct observation of the Sinhala conversation of Tamils by using recording materials. A mixed methods approach was used to analyze the necessary data. This study has classified the types of errors based on the surface structure taxonomy of errors namely, substitution, omission, addition and word ordering. Through this approach, ten sub-types of errors have been identified. Further, the findings related to the types of errors have been compared with causes of those errors. Finally, this study has revealed the actual errors made by Tamil natives in speaking Sinhala. Thus, preparing appropriate teaching and learning material that can support Tamils who wish to learn Sinhala can be considered an outcome of this research.
Keywords: Error analysis; Speaking Sinhala of Tamils; Errors in case formation; Applied linguistics